A gendered 1993-94 Social Accounting Matrix for Bangladesh - Fontana, Marzia; Wobst, Peter (International Food Policy Research Institute, 2001)
This working paper documents the construction of a 1993-94 Social Accounting Matrix (SAM) for Bangladesh. The SAM distinguishes 10 agricultural sectors —including two different kinds of rice technology — and 19 manufacturing sectors, out of 43 sectors in total. It also differentiates between twelve socio-economic groups, allowing detailed analysis of household welfare and poverty. The SAM has ten factors of production: one type of capital, one type of land and eight different types of labor which are disaggregated by both level of education and gender. The innovative feature of the SAM is that it separates out female and male labor value-added for each educational level and in eachsector of the economy, providing a base for gender-sensitive analyses of policy changes. The SAM is estimated with a cross-entropy approach, which makes efficient use of all available data in a framework that incorporates prior information and constraints.